The Ship Optimalization Model at The Pemenang Port in West Lombok Regency - Chairul Insani Ilham (IWJ : Inland Waterways Journal, 2020)
Pemenang of the harbor is one of the Ports located in West Lombok regency. Seaport Village Pemenang connect with the three Gili. Gili Air, Gili Meno and Gili Trawangan, Gili where to go to the third can not be by road, but the number of boats are available at the Port Pemenang does not match the number of passengers at the Port so that the ship - its can not operate every day. The analysis used in analyzing the existing problems in the Pemenang's Port is: Load Factor Analysis, Needs Analysis of the Canoe Motor Boat. Based on the results obtained from the data analysis needs of an ideal Canoe Motor Boat operating in the Port Ward Pemenang of Gili Air trajectory for the year 2008 as many as four ships, with restrictions on the number of trips for each trip is 2 - each ship.